The Mediating Role Of Strengthened Organizational Culture In The Relationship Between Motivation, Job Satisfaction, And Organizational Commitment On Performance In Higher Education Institutions - Suchyadi, Yudhie; Nasution, Yan Noviar; Martha , Layung Paramesti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the mediating role of organizational culture in the relationship between work motivation, job satisfaction, and organizational commitment on organizational performance at Universitas Pakuan. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires distributed to 150 permanent lecturers selected using purposive sampling. The research instrument was tested for validity and reliability, and data were analyzed using multiple linear regression and Sobel test for mediation through SPSS software. The results show that work motivation, job satisfaction, and organizational commitment have a positive and significant effect on organizational performance. These three variables also significantly influence organizational culture. Mediation analysis reveals that organizational culture significantly mediates the relationship between motivation, satisfaction, and commitment with organizational performance. These findings indicate that strengthening organizational culture plays a critical role in optimizing the impact of psychological factors on performance outcomes. The practical implication of this study suggests that enhancing organizational culture should become a key strategy in human resource development in higher education institutions. The study also contributes theoretically to the performance management literature in the academic sector and opens avenues for further exploration using qualitative approaches.